Could excessive production of tyramine by the microbiota be a reason for essential hypertension? - Aydin, Suna; Ugur, Kader; Aydin, Suleyman (Bmfh Press, 2018)
[Abstract Not Available]
Keywords: Gut Microbiota; Obesity